Instrument and System for Evaluating Thermal Regulation Properties of Textiles - Bao-guo Yao; Jian-chao Wang; Shui-yuan Hong; Li-xia Yan (Institute of Advanced Engineering and Science, 2014)
A test instrument was developed and the testing method was proposed to characterize the thermal regulation properties of textiles based on the mechanical device, microelectronics, sensors and control system. A series of indices were defined based on the typical heat flow-time curve and the raw data to characterize the thermal regulation performance of textiles. The measurement principle, the mechanical device and the evaluation method for the thermal regulation properties of textiles were introduced. Twelve types of fabrics made from different textile materials were tested. The one-way ANOVA analysis was conducted to identify the significance of the differences of the indices among the fabrics. The results show that each index is significantly different (P<0.05) among the different sample fabrics. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.5497